THE ANALYSIS OF L1 GENE VARIABILITY OF HUMAN PAPILLOMA VIRUS TYPE 16 IN OUR POPULATION - Milošević, Filip; Gatarić, Nina; Knezevic, Aleksandra (Medicinski podmladak, 2023)
Introduction: Human papilloma viruses (HPV) have been identified as a major etiological factor in the pathogenesis of cervical cancer. High-risk type HPV16 has the greatest medical significance. Based on the differences in the nucleotide sequence of the type 16 genome, the existence of 16 variants of this type with different geographical distribution has been shown. Aim: Examination of the nucleotide sequence variability of the L1 gene presented in HPV16 variants in our territory. Material and methods: The paper includes 37 sequences of HPV16 L1 genes taken from the database of the Institute of Microbiology and Immunology of the Medical Faculty, University of Belgrade. The sequences were compared with the reference sequences of the HPV16 variants and the construction of the phylogenetic tree was done using the MEGA (Molecular Evolutionary Genetics Analysis, version X) software package. Results: Out of the 37 HPV16 L1 gene sequences analyzed, 23 were grouped with European variants. Other isolates were grouped with non-European HPV16 variants. The nucleotide distance was less than 1%, that is, at the level of subvariants. Conclusion: The results of this study indicate that the European variants of the HPV16 virus are the most common in our population, but they also indicate the presence of non-European variants. Further analysis is necessary in order to monitor the circulation of HPV16 variants in our population. Keywords: Human papilloma virus, HPV16, L1 gene, phylogenetic analysis